The United Nations - Luard, Evan. author. aut Link
X, 203 p.
Keywords: 'This book is exactly what the subtitle indicates. It is a highly knowledgeable, realistic - yet positive - review and assessment of the United Nations. Convenient for use in courses on international organization. The reviewer would particularly recommend it to individuals connected officially or otherwise professionally concerned with the United Nations'. American Journal of International Law In the first edition of this book the late Evan Luard questioned whether or not the UN had failed and suggested ways in which the institution could be improved. Into this context he placed analyses of the operation of the Security Council, the General Assembly, economic and social bodies, the World Court and the International Law Commission, the Secretariat and the budget. In preparing this new edition Derek Heater has up-dated the core material and written a new concluding chapter showing how, since the mid- 1980s, the UN has perhaps been acquiring a new lease of life.